Detection of Streptococcus pyogenes virulence genes in Streptococcus dysgalactiae subsp. equisimilis from Vellore, India - Babbar, Anshu; Itzek, Andreas; Pieper, Dietmar H; Nitsche-Schmitz, D Patric (Folia microbiologica, 2018)
Streptococcus dysgalactiae subsp. equisimilis (SDSE), belonging to the group C and G streptococci, are human pathogens reported to cause clinical manifestations similar to infections caused by Streptococcus pyogenes. To scrutinize the distribution of gene coding for S. pyogenes virulence factors in SDSE, 255 isolates were collected from humans infected with SDSE in Vellore, a region in southern India, with high incidence of SDSE infections. Initial evaluation indicated SDSE isolates comprising of 82.35% group G and 17.64% group C. A multiplex PCR system was used to detect 21 gene encoding virulence-associated factors of S. pyogenes, like superantigens, DNases, proteinases, and other immune modulatory toxins. As validated by DNA sequencing of the PCR products, sequences homologous to speC, speG, speH, speI, speL, ssa and smeZ of the family of superantigen coding genes and for DNases like sdaD and sdc were detected in the SDSE collection. Furthermore, there was high abundance (48.12% in group G and 86.6% in group C SDSE) of scpA, the gene coding for C5a peptidase in these isolates. Higher abundance of S. pyogenes virulence factor genes was observed in SDSE of Lancefield group C as compared to group G, even though the incidence rates in former were lower. This study not only substantiates detection of S. pyogenes virulence factor genes in whole genome sequenced SDSE but also makes significant contribution towards the understanding of SDSE and its increasing virulence potential.
Keywords: Virulence Factors; Streptococcus; streptokokové infekce; DNA bakterií; bakteriální geny; India; Reproducibility of Results; DNA, Bacterial; lidé; Molecular Sequence Data; superantigeny; Genome, Bacterial; Superantigens; genom bakteriální; multiplexová polymerázová řetězová reakce; Streptococcus pyogenes; Multiplex Polymerase Chain Reaction; reprodukovatelnost výsledků; molekulární sekvence - údaje; Streptococcal Infections; Genes, Bacterial; Indie; faktory virulence; Humans